Plugging Means of Spreading Drugs through Punishments and the Precautionary Procedures: A Legal Juristic Study - Fadi Soud Suleiman Aljbour (دراسات: علوم الشريعة والقانون, 2021)
This study discusses a significant issue that threaten the community which is  the means leading to spreading drugs, and the role of Islamic Shariah (Law) and the Positive Laws in plugging these means through punishments and precautionary procedures. It employed the descriptive, inductive and analytical method, and deduced that plugging means is a guide from the considerable legal guides, and that drugs are legally prohibited and lawfully banned, so it is a must to plug the means of spreading drugs. This is what the Jordanian Legislator did in similar cases through legislating punishments and the precautionary procedures. It also pin-pointed that these legislations do not contradict with the Islamic Shariah, but the Islamic Shariah gives a large space for the judge in choosing the type of punishment and its severity unless surpassing the limits of the Al-Mighty Gods limits and the study recommended some recommendations. The study cocluded that positive law is a material law and deals according to (no crime and no punishment except by text), while the Islamic Sharia is a divine law, and taking it by (blocking pretexts), which notes the fate, makes it criminalize any pretext that leads to the spread of drugs, even if it is not provided for by the law, and the judge may impose the punishment that is commensurate with the type of crime.